An environment-friendly saline-alkali soil conditioner and a preparation method thereof
Patent Information
- Application Number
- CN202611455214.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-23
AI Technical Summary
[0042]通过在多孔生物炭骨架上原位负载UiO-66-NH2,利用其亚纳米级孔窗形成离子尺寸筛分环境,并结合短链聚醚构建的含氧弱配位位点及局部水合环境调控作用,提高Na+进入孔道并被可逆捕获的能力,同时降低Ca2+/Mg2+的竞争进入。
Smart Images

Figure CN122959042A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of soil conditioner technology, specifically referring to an environmentally friendly saline-alkali soil conditioner and its preparation method. Background Technology
[0002] Saline-alkali land is a type of degraded soil formed by the accumulation of soluble salts and excessively high exchangeable sodium content. Its main characteristics include increased soil electrical conductivity, increased pH, destruction of soil aggregate structure, and difficulty in water absorption by plant roots. Among these characteristics, sodium ions (Na+) in saline-alkali soils... + Excessive accumulation is one of the important factors limiting soil productivity. Soil colloids usually carry a negative charge on their surface and can adsorb Ca through electrostatic interactions. 2+ Mg 2+ K + Na + Exchangeable cations. When Na in the soil environment... + When the content is high, due to Na + With a large hydration radius and low charge density, it has a relatively weak binding ability on the surface of soil colloids, but a large amount of Na... + It will occupy soil colloid exchange sites, causing Ca 2+ and Mg 2+ Divalent cations that are beneficial to maintaining soil structure are gradually replaced, leading to the dispersion of soil colloids, destruction of aggregates, reduction of porosity and decrease in water permeability, which further causes soil compaction and hinders plant growth.
[0003] Currently, saline-alkali land improvement mainly employs methods such as irrigation to leach salt, application of gypsum-based amendments, organic matter amendment, and remediation using mineral adsorption materials. Among these, divalent cation source materials such as calcium sulfate (CaSO4) and magnesium sulfate (MgSO4) are particularly effective due to their ability to release Ca2+. 2+ and Mg 2+ Na, which promotes its adsorption with soil colloids + Ion exchange occurs, thus it is widely used in the improvement of saline-alkali soils. Its basic process is: Ca... 2+ and Mg 2+ After entering the soil solution, it exchanges Na with soil colloid exchange sites. + Competitive adsorption occurs, causing Na + Released from the exchange site, it migrates away from the root zone with water. However, existing Ca... 2+ / Mg 2+ The improved method still has some shortcomings: on the one hand, Ca 2+ and Mg 2+ After release, it is difficult to maintain sustained control, and it is prone to rapid dissolution and consumption within a short period of time, resulting in a short duration of improvement effect; on the other hand, the released Ca... 2+ and Mg2+ Will be with Na + They coexist in soil solution and readily combine with Na. + Competition for capture materials reduces Na + Targeted removal efficiency.
[0004] For Na in saline-alkali soil + To address the migration and removal issues, existing technologies further utilize porous mineral materials such as biochar, zeolite, and montmorillonite as ion adsorbents. These materials leverage the negatively charged sites and pore structure on their surfaces to remove Na+. + Adsorption. However, traditional porous adsorption materials typically rely on surface charge interactions or non-selective ion exchange to adsorb cations, which are limited in their adsorption of Na+. + Ca 2+ and Mg 2+ Many cations, such as Ca, lack significant selectivity. In actual saline-alkali soil environments, due to the... 2+ and Mg 2+ With higher charge density and stronger electrostatic interaction, it tends to preferentially occupy adsorption sites, thereby reducing Na+ adsorption capacity. + Effective capture capability of Na. Therefore, how to achieve effective capture of Na in complex multi-ion competition environments is a key issue. + Prioritized identification and selective capture are key issues for the further development of saline-alkali land improvement materials. Summary of the Invention
[0005] To address the above issues and overcome the shortcomings of existing technologies, this invention provides an environmentally friendly saline-alkali soil conditioner and its preparation method. This invention utilizes Na... + Selective capture kernel, porous biochar isolation layer, Ca 2+ / Mg 2+ The spatial structure of the slow-release layer, along with UiO-66 sub-nanometer sieving, local hydration environment regulation, and weak coordination, enables the release of Na+ in soil colloids. + Through continuous replacement, directional migration, and selective capture, sodium removal efficiency in saline-alkali soils is improved and calcium levels are reduced. 2+ / Mg 2+ compete.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The present invention proposes an environmentally friendly saline-alkali soil conditioner, wherein the soil conditioner includes Na + Selective capture kernel, located in the Na + Selective capture of the porous biochar isolation layer outside the core and Ca located outside the porous biochar isolation layer 2+ / Mg 2+ Sustained-release layer;
[0007] Preferably, the Na +The selective trapping core comprises a porous biochar framework and a functionalized UiO-66 material loaded on the porous biochar framework. The functionalized UiO-66 material has a sub-nanometer pore structure and oxygen-containing weak coordination sites at the pore openings and / or accessible pore regions.
[0008] Preferably, the functionalized UiO-66 material, through sub-nanometer pore size sieving, pore local hydration environment regulation, and oxygen-containing weak coordination, enhances the ability to control Na+. + To achieve selective mass transfer and reversible capture, and reduce Ca 2+ and Mg 2+ Entering the Na + The proportion of selective kernel capture;
[0009] Preferably, the functionalized UiO-66 material is UiO-66-NH2, and the effective pore size corresponding to the crystal window of UiO-66-NH2 is 0.5~0.7nm;
[0010] Preferably, the pores and / or accessible pore regions of the UiO-66-NH2 are grafted with short-chain polyethers, which are covalently linked to the amino sites of the UiO-66-NH2, and the ether oxygen in the short-chain polyether constitutes the oxygen-containing weak coordination sites.
[0011] Preferably, the short-chain polyether is carboxyl-terminated polyethylene glycol, and the number-average molecular weight of the carboxyl-terminated polyethylene glycol is 200-600.
[0012] Preferably, the mass of the short-chain polyether is 1-10% of the mass of UiO-66-NH2, more preferably 2-6%;
[0013] Preferably, the porous biochar has a BET specific surface area of 500-1200 m². 2 / g, and has a hierarchical pore structure composed of micropores and mesopores, of which mesopores account for 50-70% of the total pore volume;
[0014] Preferably, the Ca 2+ / Mg 2+ The sustained-release layer includes Ca 2+ Source and Mg 2+ Source, used to slowly release Ca under the action of soil water. 2+ and Mg 2+ , making Ca 2+ and Mg 2+ Na+ exchange sites with soil colloids + Ion exchange occurs to promote the adsorption of Na by soil colloids. + release;
[0015] Preferably, the porous biochar insulating layer is used to reduce the Ca content. 2+ / Mg 2+ Ca released by the sustained-release layer 2+ and Mg 2+ Directly enter the Na + Selectively captures the mass transfer rate of the nucleus, while simultaneously releasing Na from soil colloids. + To the Na + Selective capture kernel migration provides a mass transfer channel;
[0016] Preferably, the Ca 2+ / Mg 2+ The sustained-release layer includes one or both of calcium sulfate and magnesium sulfate;
[0017] Preferably, the Ca 2+ / Mg 2+ The sustained-release layer also includes a sustained-release coating material coated on the surface of calcium sulfate and / or magnesium sulfate particles, wherein the sustained-release coating material is at least one of porous biochar, starch-based material, cellulose-based material, and natural polymer material;
[0018] Preferably, the Ca 2+ / Mg 2+ Ca in the sustained-release layer 2+ Source and Mg 2+ The mass ratio of the source is 10:1 to 1:10;
[0019] Preferably, the soil conditioner has a core-shell structure, and the Na... + The selectively trapping core is located at the center of the particle, and the porous biochar isolation layer is located within the Na+. + Selective capture kernel and Ca 2+ / Mg 2+ Between the sustained-release layers, the Ca 2+ / Mg 2+ The slow-release layer forms the outer shell of the soil conditioner;
[0020] Preferably, the Na + The selectively trapping kernel has a particle size of 0.2~1.0 mm, and the porous biochar isolation layer has a thickness of 0.05~0.5 mm. 2+ / Mg 2+ The thickness of the sustained-release layer is 0.1~1.0 mm;
[0021] Ca in soil conditioners 2+ / Mg 2+ The slow-release layer has a water-permeable structure to allow soil water to enter the Ca 2+ / Mg 2+ Sustained-release layer and promotes Ca 2+ and Mg2+ release;
[0022] Preferably, the Na + Selective capture kernel for Na + Ca 2+ and Mg 2+ The multi-ion competing system constitutes Na + Preferred adsorption characteristics;
[0023] Soil conditioners undergo a directional ion migration process under the influence of soil water: Ca 2+ and Mg 2+ From Ca 2+ / Mg 2+ The slow-release layer migrates into the soil colloids and replaces the Na adsorbed by the soil colloids. + The released Na + Through the porous biochar isolation layer to Na + Selective capture of kernel migration, and selective capture via the functionalized UiO-66 material;
[0024] This invention also provides a method for preparing an environmentally friendly saline-alkali soil conditioner, which specifically includes the following steps:
[0025] S1. Preparation of porous biochar: The biomass raw material is pyrolyzed and carbonized to obtain initial biochar, and the initial biochar is activated by an activator to obtain porous biochar.
[0026] Preferably, in step S1, the biomass raw material is pyrolyzed at 450~600℃ under an inert atmosphere for 1~3h; the initial biochar and activator are activated at a mass ratio of 1:1~1:3, the activation temperature is 650~750℃, and the activation time is 1-1.5h.
[0027] Preparation of S2 and UiO-66-NH2 precursor solutions: Zirconium source, 2-aminoterephthalic acid and regulator are added to an organic solvent and mixed to obtain UiO-66-NH2 precursor solution;
[0028] Preferably, in step S2, the molar ratio of the zirconium source to 2-aminoterephthalic acid is 1:0.8 to 1:1.2, and the molar ratio of the regulator to the zirconium source is 20 to 60:1.
[0029] S3, UiO-66-NH2 in-situ loading: The porous biochar prepared in step S1 is added to the UiO-66-NH2 precursor solution prepared in step S2, so that UiO-66-NH2 can be nucleated and grown in-situ on the surface of the porous biochar and / or the pore entrance region to obtain Biochar@UiO-66-NH2 composite material.
[0030] Preferably, in step S3, the mass ratio of porous biochar to UiO-66-NH2 in the obtained Biochar@UiO-66-NH2 composite material is 1:0.2 to 1:1;
[0031] Preferably, in step S3, the in-situ nucleation growth temperature is 100~140℃ and the time is 12~36h;
[0032] S4, UiO-66-NH2 activation: The Biochar@UiO-66-NH2 composite material prepared in step S3 is washed, solvent replaced and vacuum activated to remove residual solvent in the pores and form a microporous structure that can be used for ion transport.
[0033] S5. Pore Functionalization: The Biochar@UiO-66-NH2 composite material activated in step S4 is coupled with a carboxyl-terminated short-chain polyether, causing some of the short-chain polyether to be covalently grafted onto the amino sites of UiO-66-NH2, forming oxygen-containing weak coordination sites, to obtain Na. + Selective material capture;
[0034] Preferably, in step S5, the grafting amount of the short-chain polyether is 2 to 6% of the mass of UiO-66-NH2, so that the short-chain polyether is distributed at a low density in the pores and / or accessible pore areas of UiO-66-NH2.
[0035] S6, Na + Selective core shaping: The Na prepared in step S5 + Selective capture of materials is granulated and shaped to obtain Na. + Selectively capture the kernel;
[0036] S7. Construction of the porous biochar isolation layer: The porous biochar prepared in step S1 is made into a biochar slurry with a mass concentration of 10%. The Na prepared in step S6 is then... + Selective capture nuclei are placed in a fluidized bed and spray-coated with biochar slurry, allowing Na+ to be captured. + A porous biochar isolation layer is formed on the surface of the selectively captured kernel, and then dried for later use.
[0037] S8. Soil conditioner molding and post-treatment: Ca... 2+ Source and Mg 2+ Sources were mixed, and a slow-release coating material was added to prepare Ca. 2 + / Mg 2+ Slow-release coated slurry, which contains Na treated in step S7 + Selective capture particles are placed in a fluidized bed and Ca is captured by spray coating. 2+ / Mg2+ Slow-release coated slurry is applied to the outside of the porous biochar isolation layer. After coating, Ca is formed. 2+ / Mg 2+ Slow-release layer, dried, yields an environmentally friendly saline-alkali soil conditioner;
[0038] Preferably, in step S8, the Ca 2+ Source, Mg 2+ The mass ratio between the source and the sustained-release coating material is 10:1:0.8 to 1:10:1.2;
[0039] Preferably, in step S8, the Ca 2+ / Mg 2+ The solid content of the slow-release coated slurry is 45-55%.
[0040] This invention provides an environmentally friendly saline-alkali soil conditioner and its preparation method. This invention utilizes Na... + Selective capture kernel, porous biochar isolation layer, Ca 2+ / Mg 2+ The spatial structure of the slow-release layer, along with UiO-66 sub-nanometer sieving, local hydration environment regulation, and weak coordination, enables the release of Na+ in soil colloids. + Through continuous replacement, directional migration, and selective capture, sodium removal efficiency in saline-alkali soils is improved and calcium levels are reduced. 2+ / Mg 2+ compete.
[0041] The beneficial effects achieved by this invention are as follows:
[0042] By in-situ loading UiO-66-NH2 onto a porous biochar framework, an ion-size sieving environment is created using its sub-nanometer pore windows. Combined with the oxygen-containing weak coordination sites constructed from short-chain polyethers and the regulation of the local hydration environment, the Na+ ion-sieving environment is enhanced. + The ability to enter the channel and be reversibly trapped, while reducing Ca. 2+ / Mg 2+ The competition has entered.
[0043] Through Na + Selective capture kernel and Ca 2+ / Mg 2+ A porous biochar separator layer is placed between the sustained-release layers to increase Ca content. 2+ and Mg 2+ Mass transfer resistance to migration to the kernel causes Ca 2+ Mg 2+ It can release and participate in the production of Na into the external soil environment. + Replacement, while reducing its entry into Na + Selective capture of the kernel, thereby maintaining kernel Na. + Selectivity.
[0044] Ca 2+ / Mg 2+ The sustained-release layer continuously releases Ca 2+ and Mg 2+ Na+ exchange sites with soil colloids + Ion exchange occurs, causing adsorbed Na to... + Release; released Na + Through the porous biochar isolation layer to Na + Selective capture of kernel migration, and capture by functionalized UiO-66 material, thereby forming Ca 2+ / Mg 2+ Outward release displacement, Na + The directional migration process of trapped ions that migrate inward.
[0045] CaSO4 and MgSO4 are used as Ca 2+ Mg 2+ The source is controlled by a slow-release coating material to regulate the dissolution rate of Ca. 2+ and Mg 2 + It can continuously participate in soil colloidal cation exchange, avoiding excessive Ca... 2+ / Mg 2+ The rapid consumption caused by short-term release helps to prolong the sodium removal time in the soil.
[0046] Porous biochar possesses a high specific surface area and hierarchical pore structure, providing a loading framework and rapid mass transfer channels for UiO-66-NH2 on the one hand, and improving soil pore structure and water migration conditions on the other, which is beneficial to Na+. + It migrates into the soil amendment along with the soil water.
[0047] By using core-shell spatial partitioning, Na + Selective capture region and Ca 2+ / Mg 2+ The release area is physically isolated to prevent Ca 2+ Mg 2+ Direct contact with Na + Selective materials occupy effective capture sites; with Ca 2+ / Mg 2+ Source and Na + Compared to the selective direct mixing of materials, this method can improve Na + Effective capture ratio.
[0048] The biochar, calcium sulfate, magnesium sulfate, and biodegradable coating materials used can all be used to construct composite soil amendment particles in the soil environment. While achieving sodium removal from saline-alkali soil, it can reduce the dependence on high-intensity chemical treatment methods and is suitable for the continuous improvement of saline-alkali root zones. Attached Figure Description
[0049] Figure 1 Na is used in the embodiments and comparative examples of the present invention. + Ca 2+ and Mg 2+ Graph showing the residual concentration in the filtrate;
[0050] Figure 2 Na is used in the embodiments and comparative examples of the present invention. + Ca 2+ and Mg 2+ Adsorption capacity results graph;
[0051] Figure 3 The soil conditioners prepared for the embodiments and comparative examples of this invention have the following effects on Na+. + Graph showing the results of selective adsorption;
[0052] Figure 4 Na in the soil conditioners prepared for the embodiments and comparative examples of the present invention + Ca 2+ and Mg 2+ Migration rate results graph.
[0053] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the embodiments of the invention to explain the invention and do not constitute a limitation thereof. Detailed Implementation
[0054] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to this invention. The preferred embodiments and materials described herein are for illustrative purposes only and do not limit the scope of this application.
[0056] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the experimental materials and test strains used in the following examples were purchased from commercial channels.
[0057] Example 1
[0058] This embodiment provides an environmentally friendly saline-alkali soil conditioner, which comprises, from the inside out, Na. + Selective trapping kernel, porous biochar isolation layer and Ca 2+ / Mg 2+ Sustained-release layer, in which Na + The selective capture kernel was constructed by loading UiO-66-NH2 onto porous biochar and further functionalizing the pore regions with carboxyl-terminated polyethylene glycol.
[0059] This embodiment also provides a method for preparing an environmentally friendly saline-alkali soil conditioner, which specifically includes the following steps:
[0060] S1. Preparation of porous biochar: Corn stalks were selected as biomass raw material, crushed to a particle size of less than 2 mm, and then pyrolyzed and carbonized under a nitrogen atmosphere. The corn stalks were placed in a tube furnace and heated to 550°C at a heating rate of 5°C / min, held for 2 h, and cooled to obtain initial biochar. The obtained initial biochar was mixed with KOH at a mass ratio of 1:2, and deionized water was added to make a uniform slurry. The slurry was placed in a nitrogen atmosphere and heated to 700°C at a heating rate of 5°C / min, held for 1 h for activation. After activation, the slurry was naturally cooled, washed with 0.1 mol / L hydrochloric acid aqueous solution, and then washed with deionized water until the pH of the washing solution was 7.0. The slurry was then dried at 105°C for 12 h to obtain porous biochar.
[0061] Preparation of S2 and UiO-66-NH2 precursor solutions: Zirconium chloride was used as the zirconium source, 2-aminoterephthalic acid was used as the organic ligand, DMF was used as the reaction solvent, and glacial acetic acid was used as the regulator. Zirconium chloride and 2-aminoterephthalic acid were weighed according to the molar ratio of zirconium chloride: 2-aminoterephthalic acid = 1:1. Glacial acetic acid was added according to the molar ratio of glacial acetic acid: zirconium chloride = 40:1. The above components were added to DMF and stirred at room temperature for 60 min to ensure that the components were fully mixed to obtain the UiO-66-NH2 precursor solution.
[0062] S3, UiO-66-NH2 in-situ loading: 10g of the porous biochar obtained in step S1 was added to the UiO-66-NH2 precursor solution obtained in step S2. After ultrasonic dispersion for 30min, mechanical stirring was performed for 1h to allow the precursor to fully enter the mesoporous structure of the porous biochar. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and reacted at 120℃ for 24h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid product was obtained by centrifugation. The solid product was washed three times with DMF and three times with anhydrous methanol to remove unreacted organic ligands and residual reactants, thus obtaining the Biochar@UiO-66-NH2 composite material. The mass ratio of porous biochar to UiO-66-NH2 was 1:0.5.
[0063] S4, UiO-66-NH2 activation: The Biochar@UiO-66-NH2 composite material obtained in step S3 was added to methanol for solvent replacement. The methanol was replaced every 12 hours for a total of 3 times. The material was then filtered, pre-dried at 80°C for 6 hours, and then activated at 120°C under vacuum for 12 hours to remove the residual solvent in the UiO-66-NH2 channels, thus obtaining the Biochar@UiO-66-NH2 composite material with open channels.
[0064] S5. Pore Functionalization: Carboxyl-terminated polyethylene glycol (PEG) was used as a short-chain polyether. The number-average molecular weight of the PEG was 400. 10g of the Biochar@UiO-66-NH2 composite material was dispersed in MES buffer, and 0.4g of PEG was added. EDC and NHS were added as condensing agents, and the pH of the system was adjusted to 5.5. The reaction was carried out at 25℃ for 8h, allowing the carboxyl groups of the PEG to undergo a coupling reaction with the amino groups on the surface and in the accessible regions of UiO-66-NH2. After the reaction, the mixture was thoroughly washed with deionized water and then dried under vacuum at 50℃ to obtain Na. + Selective trapping material, wherein the grafting amount of short-chain polyether is 4% of the mass of UiO-66-NH2;
[0065] S6, Na + Selective capture kernel shaping: The Na obtained in step S5 + Selective capture material is mixed with deionized water and granulated by wet granulation. After granulation, Na is separated by sieving. + Selectively capturing kernels with a diameter of 0.65 mm and drying them at 60 °C for 12 h yielded Na. + Selectively capture the kernel;
[0066] S7. Construction of porous biochar isolation layer: The porous biochar obtained in step S1 is made into a biochar slurry with a mass concentration of 10%. The Na obtained in step S6 is then... +Selective capture nuclei are placed in a fluidized bed and spray-coated with biochar slurry. The spray rate and number of coating cycles are adjusted to control Na+ content. + A porous biochar isolation layer with a thickness of 0.20 mm was formed on the surface of the selectively captured kernel, and then dried at 60℃ for 6 hours after coating.
[0067] S8. Soil conditioner molding and post-treatment: Calcium sulfate and magnesium sulfate are mixed, and starch is added as a slow-release coating material. The mass ratio of calcium sulfate, magnesium sulfate, and starch is 3:1:1. Deionized water is added, and the mixture is stirred at 500 rpm for 30 minutes to obtain Ca... 2+ / Mg 2+ Slow-release coated slurry with a solid content of 50% will form a porous biochar isolation layer containing Na. + Selective capture particles are placed in a fluidized bed and Ca is captured by spray coating. 2+ / Mg 2+ Slow-release coated slurry is applied to the outside of the porous biochar isolation layer, forming a Ca layer with a thickness of 0.50 mm depending on the coating amount. 2+ / Mg 2+ After the slow-release layer is coated, it is dried at 60℃ for 12 hours. After sieving to remove agglomerated particles, an environmentally friendly saline-alkali soil conditioner is obtained.
[0068] Example 2
[0069] This embodiment provides an environmentally friendly saline-alkali soil conditioner, which comprises, from the inside out, Na. + Selective trapping kernel, porous biochar isolation layer and Ca 2+ / Mg 2+ Sustained-release layer, in which Na + The selective capture kernel was constructed by loading UiO-66-NH2 onto porous biochar and further functionalizing the pore regions with carboxyl-terminated polyethylene glycol.
[0070] This embodiment also provides a method for preparing an environmentally friendly saline-alkali soil conditioner, which specifically includes the following steps:
[0071] S1. Preparation of porous biochar: Corn stalks were selected as biomass raw material, crushed to a particle size of less than 2 mm, and then pyrolyzed and carbonized under a nitrogen atmosphere. The corn stalks were placed in a tube furnace and heated to 500℃ at a heating rate of 5℃ / min, and held for 3 h. After cooling, the initial biochar was obtained. The obtained initial biochar was mixed with KOH at a mass ratio of 1:1, and deionized water was added to make a uniform slurry. The slurry was placed in a nitrogen atmosphere and heated to 650℃ at a heating rate of 5℃ / min, and held for 1.5 h for activation. After activation, the slurry was naturally cooled, washed with 0.1 mol / L hydrochloric acid aqueous solution, and then washed with deionized water until the pH of the washing solution was 7.0. The slurry was then dried at 105℃ for 12 h to obtain porous biochar.
[0072] Preparation of S2 and UiO-66-NH2 precursor solutions: Zirconium chloride was used as the zirconium source, 2-aminoterephthalic acid was used as the organic ligand, DMF was used as the reaction solvent, and glacial acetic acid was used as the regulator. Zirconium chloride and 2-aminoterephthalic acid were weighed according to the molar ratio of zirconium chloride: 2-aminoterephthalic acid = 1: 0.8. Glacial acetic acid was added according to the molar ratio of glacial acetic acid: zirconium chloride = 20: 1. The above components were added to DMF and stirred at room temperature for 60 min to ensure that the components were fully mixed to obtain the UiO-66-NH2 precursor solution.
[0073] S3, UiO-66-NH2 in-situ loading: 10g of the porous biochar obtained in step S1 was added to the UiO-66-NH2 precursor solution obtained in step S2. After ultrasonic dispersion for 30min, mechanical stirring was performed for 1h to allow the precursor to fully enter the mesoporous structure of the porous biochar. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and reacted at 100℃ for 36h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid product was obtained by centrifugation. The solid product was washed three times with DMF and three times with anhydrous methanol to remove unreacted organic ligands and residual reactants, thus obtaining the Biochar@UiO-66-NH2 composite material. The mass ratio of porous biochar to UiO-66-NH2 was 1:0.2.
[0074] S4, UiO-66-NH2 activation: The Biochar@UiO-66-NH2 composite material obtained in step S3 was added to methanol for solvent replacement. The methanol was replaced every 12 hours for a total of 3 times. The material was then filtered, pre-dried at 80°C for 6 hours, and then activated at 120°C under vacuum for 12 hours to remove the residual solvent in the UiO-66-NH2 channels, thus obtaining the Biochar@UiO-66-NH2 composite material with open channels.
[0075] S5. Pore Functionalization: Carboxyl-terminated polyethylene glycol (PEG) was used as a short-chain polyether. The number-average molecular weight of the PEG was 200. 10g of the Biochar@UiO-66-NH2 composite material was dispersed in MES buffer, and 0.2g of PEG was added. EDC and NHS were added as condensing agents, and the pH of the system was adjusted to 5.5. The reaction was carried out at 20℃ for 12h to allow the carboxyl groups of the PEG to undergo a coupling reaction with the amino groups on the surface and in the accessible regions of UiO-66-NH2. After the reaction, the mixture was thoroughly washed with deionized water and then dried under vacuum at 50℃ to obtain Na. + Selective trapping material, wherein the grafting amount of short-chain polyether is 2% of the mass of UiO-66-NH2;
[0076] S6, Na +Selective capture kernel shaping: The Na obtained in step S5 + Selective capture material is mixed with deionized water and granulated by wet granulation. After granulation, Na is separated by sieving. + Selective capture of kernel particles with a diameter of 0.3 mm was performed, and the resulting particles were dried at 60 °C for 12 h to obtain Na. + Selectively capture the kernel;
[0077] S7. Construction of porous biochar isolation layer: The porous biochar obtained in step S1 is further processed into a biochar slurry with a mass concentration of 10%. The Na obtained in step S6 is then... + Selective capture nuclei are placed in a fluidized bed and spray-coated with biochar slurry. The spray rate and number of coating cycles are adjusted to control Na+ content. + A porous biochar isolation layer with a thickness of 0.05 mm was formed on the surface of the selectively captured kernel, and then dried at 60℃ for 6 hours after coating.
[0078] S8. Soil conditioner molding and post-treatment: Calcium sulfate and magnesium sulfate are mixed, and starch is added as a slow-release coating material. The mass ratio of calcium sulfate, magnesium sulfate, and starch is 1:1:1. Deionized water is added, and the mixture is stirred at 500 rpm for 30 minutes to obtain Ca... 2+ / Mg 2+ Slow-release coated slurry with a solid content of 45% will form a porous biochar isolation layer containing Na. + Selective capture particles are placed in a fluidized bed and Ca is captured by spray coating. 2+ / Mg 2+ Slow-release coated slurry is coated on the outside of the porous biochar isolation layer, forming a Ca layer with a thickness of 0.10 mm depending on the coating amount. 2+ / Mg 2+ After the slow-release layer is coated, it is dried at 50℃ for 12 hours. After sieving to remove agglomerated particles, an environmentally friendly saline-alkali soil conditioner is obtained.
[0079] Example 3
[0080] This embodiment provides an environmentally friendly saline-alkali soil conditioner, which comprises, from the inside out, Na. + Selective trapping kernel, porous biochar isolation layer and Ca 2+ / Mg 2+ Sustained-release layer, in which Na + The selective capture kernel was constructed by loading UiO-66-NH2 onto porous biochar and further functionalizing the pore regions with carboxyl-terminated polyethylene glycol.
[0081] This embodiment also provides a method for preparing an environmentally friendly saline-alkali soil conditioner, which specifically includes the following steps:
[0082] S1. Preparation of porous biochar: Wood chips were selected as biomass raw material, crushed to a particle size of less than 2 mm, and then pyrolyzed and carbonized under a nitrogen atmosphere. The wood chips were placed in a tube furnace and heated to 600℃ at a heating rate of 5℃ / min, held for 1 h, and cooled to obtain initial biochar. The obtained initial biochar was mixed with KOH at a mass ratio of 1:3, and deionized water was added to make a uniform slurry. The slurry was placed in a nitrogen atmosphere and heated to 750℃ at a heating rate of 5℃ / min, held for 1 h for activation. After activation, the slurry was naturally cooled, washed with 0.1 mol / L hydrochloric acid aqueous solution, and then washed with deionized water until the pH of the washing solution was 7.0. The slurry was then dried at 105℃ for 12 h to obtain porous biochar.
[0083] Preparation of S2 and UiO-66-NH2 precursor solutions: Zirconium chloride was used as the zirconium source, 2-aminoterephthalic acid was used as the organic ligand, DMF was used as the reaction solvent, and glacial acetic acid was used as the regulator. Zirconium chloride and 2-aminoterephthalic acid were weighed according to the molar ratio of zirconium chloride: 2-aminoterephthalic acid = 1:1.2. Glacial acetic acid was added according to the molar ratio of glacial acetic acid: zirconium chloride = 60:1. The above components were added to DMF and stirred at room temperature for 60 min to ensure that the components were fully mixed, thus obtaining the UiO-66-NH2 precursor solution.
[0084] S3, UiO-66-NH2 in-situ loading: 10g of porous biochar obtained in step S1 was added to the UiO-66-NH2 precursor solution obtained in step S2. After ultrasonic dispersion for 30min, mechanical stirring was performed for 1h to allow the precursor to fully enter the mesoporous structure of the porous biochar. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and reacted at 140℃ for 12h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged to obtain a solid product. The product was washed three times with DMF and three times with anhydrous methanol to remove unreacted organic ligands and residual reactants, thus obtaining the Biochar@UiO-66-NH2 composite material. The mass ratio of porous biochar to UiO-66-NH2 was 1:1.
[0085] S4, UiO-66-NH2 activation: The Biochar@UiO-66-NH2 composite material obtained in step S3 was added to methanol for solvent replacement. The methanol was replaced every 12 hours for a total of 3 times. The material was then filtered, pre-dried at 80°C for 6 hours, and then activated at 120°C under vacuum for 12 hours to remove the residual solvent in the UiO-66-NH2 channels, thus obtaining the Biochar@UiO-66-NH2 composite material with open channels.
[0086] S5. Pore Functionalization: Carboxyl-terminated polyethylene glycol (PEG) was used as a short-chain polyether. The number-average molecular weight of the PEG was 600. 10g of the Biochar@UiO-66-NH2 composite material was dispersed in MES buffer, and 0.6g of PEG was added. EDC and NHS were added as condensing agents, and the pH of the system was adjusted to 5.5. The reaction was carried out at 30℃ for 6h, allowing the carboxyl groups of the PEG to undergo a coupling reaction with the amino groups on the surface and in the accessible regions of UiO-66-NH2. After the reaction, the mixture was thoroughly washed with deionized water and then dried under vacuum at 50℃ to obtain Na. + Selective trapping material, wherein the grafting amount of short-chain polyether is 6% of the mass of UiO-66-NH2;
[0087] S6, Na + Selective capture kernel shaping: The Na obtained in step S5 + Selective capture material is mixed with deionized water and granulated by wet granulation. After granulation, Na is separated by sieving. + Selective capture of kernel particles with a diameter of 0.9 mm was performed, and the resulting particles were dried at 60 °C for 12 h to obtain Na. + Selectively capture the kernel;
[0088] S7. Construction of porous biochar isolation layer: The porous biochar obtained in step S1 is further processed into a biochar slurry with a mass concentration of 10%; the Na obtained in step S6 is... + Selective capture nuclei are placed in a fluidized bed and spray-coated with biochar slurry. The spray rate and number of coating cycles are adjusted to control Na+ content. + A porous biochar isolation layer with a thickness of 0.50 mm was formed on the surface of the selectively captured kernel, and then dried at 60℃ for 6 hours after coating.
[0089] S8. Soil conditioner molding and post-treatment: Calcium sulfate and magnesium sulfate are mixed, and starch is added as a slow-release coating material. The mass ratio of calcium sulfate, magnesium sulfate, and starch is 10:1:1. Deionized water is added, and the mixture is stirred at 500 rpm for 30 minutes to obtain Ca... 2+ / Mg 2+ Slow-release coated slurry with a solid content of 55% will form a porous biochar isolation layer containing Na. + Selective capture particles are placed in a fluidized bed and Ca is captured by spray coating. 2+ / Mg 2+ Slow-release coated slurry is applied to the outside of the porous biochar isolation layer, forming a 1.00 mm thick Ca layer through the coating amount. 2+ / Mg 2+ After the slow-release layer is coated, it is dried at 55℃ for 12 hours. After sieving to remove agglomerated particles, an environmentally friendly saline-alkali soil conditioner is obtained.
[0090] Example 4
[0091] This embodiment provides an environmentally friendly saline-alkali soil conditioner, which comprises, from the inside out, Na. + Selective trapping kernel, porous biochar isolation layer and Ca 2+ / Mg 2+ Sustained-release layer, in which Na + The selective capture kernel was constructed by loading UiO-66-NH2 onto porous biochar and further functionalizing the pore regions with carboxyl-terminated polyethylene glycol.
[0092] This embodiment also provides a method for preparing an environmentally friendly saline-alkali soil conditioner, which specifically includes the following steps:
[0093] S1. Preparation of porous biochar: Corn stalks were selected as biomass raw material, crushed to a particle size of less than 2 mm, and then pyrolyzed and carbonized under a nitrogen atmosphere. The corn stalks were placed in a tube furnace and heated to 550°C at a heating rate of 5°C / min, held for 2 h, and cooled to obtain initial biochar. The obtained initial biochar was mixed with KOH at a mass ratio of 1:2, and deionized water was added to make a uniform slurry. The slurry was placed in a nitrogen atmosphere and heated to 700°C at a heating rate of 5°C / min, held for 1 h for activation. After activation, the slurry was naturally cooled, washed with 0.1 mol / L hydrochloric acid aqueous solution, and then washed with deionized water until the pH of the washing solution was 7.0. The slurry was then dried at 105°C for 12 h to obtain porous biochar.
[0094] Preparation of S2 and UiO-66-NH2 precursor solutions: Zirconium chloride was used as the zirconium source, 2-aminoterephthalic acid was used as the organic ligand, DMF was used as the reaction solvent, and glacial acetic acid was used as the regulator. Zirconium chloride and 2-aminoterephthalic acid were weighed according to a molar ratio of zirconium chloride: 2-aminoterephthalic acid = 1:1. Glacial acetic acid was added according to a molar ratio of glacial acetic acid: zirconium chloride = 40:1. The above components were added to DMF and stirred at room temperature for 60 min to ensure that the components were fully mixed, thus obtaining the UiO-66-NH2 precursor solution.
[0095] S3, UiO-66-NH2 in-situ loading: 10g of the porous biochar obtained in step S1 was added to the UiO-66-NH2 precursor solution obtained in step S2. After ultrasonic dispersion for 30min, mechanical stirring was performed for 1h to allow the precursor to fully enter the mesoporous structure of the porous biochar. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and reacted at 120℃ for 24h. After the reaction was completed, the mixture was naturally cooled to room temperature and the solid product was obtained by centrifugation. The solid product was washed three times with DMF and three times with anhydrous methanol to remove unreacted organic ligands and residual reactants, thus obtaining the Biochar@UiO-66-NH2 composite material. The mass ratio of porous biochar to UiO-66-NH2 was 1:0.5.
[0096] S4, UiO-66-NH2 activation: The Biochar@UiO-66-NH2 composite material obtained in step S3 was added to methanol for solvent replacement. The methanol was replaced every 12 hours for a total of 3 times. The material was then filtered, pre-dried at 80°C for 6 hours, and then activated at 120°C under vacuum for 12 hours to remove the residual solvent in the UiO-66-NH2 channels, thus obtaining the Biochar@UiO-66-NH2 composite material with open channels.
[0097] S5. Pore Functionalization: Carboxyl-terminated polyethylene glycol (PEG) was used as a short-chain polyether. The number-average molecular weight of the PEG was 400. 10g of the Biochar@UiO-66-NH2 composite material was dispersed in MES buffer, and 0.4g of PEG was added. EDC and NHS were added as condensing agents, and the pH of the system was adjusted to 5.8. The reaction was carried out at 25℃ for 8h, allowing the carboxyl groups of the PEG to undergo a coupling reaction with the amino groups on the surface and in the accessible regions of UiO-66-NH2. After the reaction, the mixture was thoroughly washed with deionized water and then dried under vacuum at 50℃ to obtain Na. + Selective trapping material, wherein the grafting amount of short-chain polyether is 4% of the mass of UiO-66-NH2;
[0098] S6, Na + Selective capture kernel shaping: The Na obtained in step S5 + Selective capture material is mixed with deionized water and granulated by wet granulation. After granulation, Na is separated by sieving. + Selective capture of kernel particles with a diameter of 0.65 mm was performed, and the resulting particles were dried at 60 °C for 12 h to obtain Na. + Selectively capture the kernel;
[0099] S7. Construction of porous biochar isolation layer: The porous biochar obtained in step S1 is further processed into a biochar slurry with a mass concentration of 10%. The Na obtained in step S6 is then... +Selective capture nuclei are placed in a fluidized bed and spray-coated with biochar slurry. The spray rate and number of coating cycles are adjusted to control Na+ content. + A porous biochar isolation layer with a thickness of 0.30 mm was formed on the surface of the selectively captured kernel, and then dried at 60℃ for 6 hours after coating.
[0100] S8. Soil conditioner molding and post-treatment: Calcium sulfate and magnesium sulfate are mixed, and starch is added as a slow-release coating material. The mass ratio of calcium sulfate, magnesium sulfate, and starch is 1:10:1. Deionized water is added, and the mixture is stirred at 500 rpm for 30 minutes to obtain Ca... 2+ / Mg 2+ Slow-release coated slurry with a solid content of 55% will form a porous biochar isolation layer containing Na. + Selective capture particles are placed in a fluidized bed and Ca is captured by spray coating. 2+ / Mg 2+ Slow-release coated slurry is applied to the outside of the porous biochar isolation layer, forming a Ca layer with a thickness of 0.50 mm depending on the coating amount. 2+ / Mg 2+ After the slow-release layer is coated, it is dried at 50℃ for 12 hours. After sieving to remove agglomerated particles, an environmentally friendly saline-alkali soil conditioner is obtained.
[0101] Example 5
[0102] This embodiment provides an environmentally friendly saline-alkali soil conditioner, which comprises, from the inside out, Na. + Selective capture kernel, porous biochar isolation layer, Ca 2+ / Mg 2+ Sustained-release layer, in which Na + The selective capture kernel was constructed by loading UiO-66-NH2 onto porous biochar and further functionalizing the pore regions with carboxyl-terminated polyethylene glycol.
[0103] This embodiment also provides a method for preparing an environmentally friendly saline-alkali soil conditioner, which specifically includes the following steps:
[0104] S1. Preparation of porous biochar: Corn stalks were selected as biomass raw material, crushed to a particle size of less than 2 mm, and then pyrolyzed and carbonized under a nitrogen atmosphere. The corn stalks were placed in a tube furnace and heated to 550°C at a heating rate of 5°C / min, held for 2 h, and cooled to obtain initial biochar. The obtained initial biochar was mixed with KOH at a mass ratio of 1:1, and deionized water was added to make a uniform slurry. The slurry was placed in a nitrogen atmosphere and heated to 700°C at a heating rate of 5°C / min, held for 1 h for activation. After activation, the slurry was naturally cooled, washed with 0.1 mol / L hydrochloric acid aqueous solution, and then washed with deionized water until the pH of the washing solution was 7.0. The slurry was then dried at 105°C for 12 h to obtain porous biochar.
[0105] Preparation of S2 and UiO-66-NH2 precursor solutions: Zirconium chloride was used as the zirconium source, 2-aminoterephthalic acid was used as the organic ligand, DMF was used as the reaction solvent, and glacial acetic acid was used as the regulator. Zirconium chloride and 2-aminoterephthalic acid were weighed according to a molar ratio of zirconium chloride: 2-aminoterephthalic acid = 1:1. Glacial acetic acid was added according to a molar ratio of glacial acetic acid: zirconium chloride = 40:1. The above components were added to DMF and stirred at room temperature for 60 min to ensure that the components were fully mixed, thus obtaining the UiO-66-NH2 precursor solution.
[0106] S3, UiO-66-NH2 in-situ loading: 10g of the porous biochar obtained in step S1 was added to the UiO-66-NH2 precursor solution obtained in step S2. After ultrasonic dispersion for 30min, mechanical stirring was performed for 1h to allow the precursor to fully enter the mesoporous structure of the porous biochar. The mixture was then transferred to a polytetrafluoroethylene-lined reactor and reacted at 120℃ for 24h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged to obtain a solid product. The product was washed three times with DMF and three times with anhydrous methanol to remove unreacted organic ligands and residual reactants, thus obtaining the Biochar@UiO-66-NH2 composite material. The mass ratio of porous biochar to UiO-66-NH2 was 1:0.4.
[0107] S4, UiO-66-NH2 activation: The Biochar@UiO-66-NH2 composite material obtained in step S3 was added to methanol for solvent replacement. The methanol was replaced every 12 hours for a total of 3 times. The material was then filtered, pre-dried at 80°C for 6 hours, and then activated at 120°C under vacuum for 12 hours to remove the residual solvent in the UiO-66-NH2 channels, thus obtaining the Biochar@UiO-66-NH2 composite material with open channels.
[0108] S5. Pore Functionalization: Carboxyl-terminated polyethylene glycol (PEG) was used as a short-chain polyether. The number-average molecular weight of the PEG was 400. 10g of the Biochar@UiO-66-NH2 composite material was dispersed in MES buffer, and 0.4g of PEG was added. EDC and NHS were added as condensing agents, and the pH of the system was adjusted to 6.0. The reaction was carried out at 25℃ for 8h, allowing the carboxyl groups of the PEG to undergo a coupling reaction with the amino groups on the surface and in the accessible regions of UiO-66-NH2. After the reaction, the mixture was thoroughly washed with deionized water and then dried under vacuum at 50℃ to obtain Na. + Selective trapping material, wherein the grafting amount of short-chain polyether is 4% of the mass of UiO-66-NH2;
[0109] S6, Na +Selective capture kernel shaping: The Na obtained in step S5 + Selective capture material is mixed with deionized water and granulated by wet granulation. After granulation, Na is separated by sieving. + Selective capture of kernel particles with a diameter of 0.7 mm was performed, and the resulting particles were dried at 60 °C for 12 h to obtain Na. + Selectively capture the kernel;
[0110] S7. Construction of porous biochar isolation layer: The porous biochar obtained in step S1 is further processed into a biochar slurry with a mass concentration of 10%. The Na obtained in step S6 is then... + Selective capture nuclei are placed in a fluidized bed and spray-coated with biochar slurry. The spray rate and number of coating cycles are adjusted to control Na+ content. + A porous biochar isolation layer with a thickness of 0.50 mm was formed on the surface of the selectively captured kernel, and then dried at 60℃ for 8 hours after coating.
[0111] S8. Soil conditioner molding and post-treatment: Calcium sulfate and magnesium sulfate are mixed, and starch is added as a slow-release coating material. The mass ratio of calcium sulfate, magnesium sulfate, and starch is 1:1:1. Deionized water is added, and the mixture is stirred at 500 rpm for 30 minutes to obtain Ca... 2+ / Mg 2+ Slow-release coated slurry with a solid content of 45% will form a porous biochar isolation layer containing Na. + Selective capture particles are placed in a fluidized bed and Ca is captured by spray coating. 2+ / Mg 2+ Slow-release coated slurry is coated on the outside of the porous biochar isolation layer, forming a Ca layer with a thickness of 0.80 mm depending on the coating amount. 2+ / Mg 2+ After the slow-release layer is coated, it is dried at 55℃ for 12 hours. After sieving to remove agglomerated particles, an environmentally friendly saline-alkali soil conditioner is obtained.
[0112] Comparative Example 1
[0113] This comparative example prepares a soil conditioner for saline-alkali land. The preparation method is basically the same as in Example 1, except that Na... + In the selective capture kernel, UiO-66-NH2 is not added; porous biochar is used solely as the Na+ precipitate. + Capture the core material to investigate the effect of the UiO-66-NH2 sub-nanopore structure on Na + The effects of selective mass transfer and capture performance, and specific preparation methods include:
[0114] S1, Same as in Example 1;
[0115] S2. The porous biochar obtained in step S1 is mixed with deionized water and granulated by wet granulation. After granulation, the particle size of the obtained particles is controlled to be 0.65 mm by sieving. The obtained particles are dried at 60°C for 12 h to obtain core particles without UiO-66-NH2.
[0116] S3. Construction of porous biochar isolation layer: Following the method in step S7 of Example 1, a porous biochar isolation layer with a thickness of 0.20 mm is formed on the surface of the core particles obtained in step S2. After coating, it is dried at 60°C for 6 hours.
[0117] S4. Soil conditioner molding and post-treatment: Following the method in step S8 of Example 1, calcium sulfate and magnesium sulfate were mixed at a mass ratio of 3:1, and starch was added as a slow-release coating material to prepare Ca... 2+ / Mg 2+ Slow-release coated slurry places the core particles that form a porous biochar isolation layer in a fluidized bed, and uses a spray coating method to coat Ca... 2+ / Mg 2+ Slow-release coated slurry was applied to the outside of the porous biochar isolation layer, and a Ca layer with a thickness of 0.50 mm was formed by controlling the coating amount. 2+ / Mg 2+ After the slow-release layer is coated, it is dried at 60℃ for 12 hours. Aggregated particles are removed by sieving to obtain the soil conditioner for saline-alkali land.
[0118] Comparative Example 2
[0119] This comparative example prepares a core-shell structured saline-alkali soil conditioner. The preparation method is basically the same as in Example 1, except that the Biochar@UiO-66-NH2 composite material is not subjected to carboxyl-terminated polyethylene glycol functionalization. The specific preparation method includes:
[0120] S1. Preparation of porous biochar: Porous biochar was prepared according to the method in step S1 of Example 1;
[0121] S2, Preparation of UiO-66-NH2 precursor solution: The UiO-66-NH2 precursor solution was prepared according to the method in step S2 of Example 1;
[0122] S3, In-situ loading of UiO-66-NH2: Following the method in step S3 of Example 1, porous biochar was added to the UiO-66-NH2 precursor solution and reacted at 120°C for 24 h to allow UiO-66-NH2 to nucleate and grow in situ on the surface of the porous biochar and / or in the pore entrance region, thus obtaining the Biochar@UiO-66-NH2 composite material; the mass ratio of porous biochar to UiO-66-NH2 was controlled to be 1:0.5.
[0123] S4, UiO-66-NH2 activation: The Biochar@UiO-66-NH2 composite material was subjected to solvent replacement and vacuum activation treatment according to the method in step S4 of Example 1 to obtain the Biochar@UiO-66-NH2 composite material with open channels.
[0124] S5, Na + Selective core capture molding: Without performing the carboxyl-terminated polyethylene glycol coupling step in Example 1, the Biochar@UiO-66-NH2 composite material obtained in step S4 was mixed with deionized water and granulated by wet granulation. After granulation, Na+ was controlled by sieving. + Selective capture of 0.65 mm kernel particles was performed, and the resulting particles were dried at 60 °C for 12 h to obtain un-PEG-functionalized Na. + Selectively capture the kernel;
[0125] S6. Construction of porous biochar isolation layer: Following the method in step S7 of Example 1, the Na obtained in step S5... + A porous biochar isolation layer with a thickness of 0.20 mm was formed on the surface of the selectively captured kernel, and then dried at 60℃ for 6 hours after coating.
[0126] S7. Soil conditioner molding and post-treatment: Following the method in step S8 of Example 1, calcium sulfate and magnesium sulfate were mixed at a mass ratio of 3:1, and starch was added as a slow-release coating material to prepare Ca... 2+ / Mg 2+ Slow-release coated slurry will form a porous biochar isolation layer of Na + Selective capture particles are placed in a fluidized bed and Ca is captured by spray coating. 2+ / Mg 2+ Slow-release coated slurry was applied to the outside of the porous biochar isolation layer, and a Ca layer with a thickness of 0.50 mm was formed by controlling the coating amount. 2+ / Mg 2+ After the slow-release layer is coated, it is dried at 60℃ for 12 hours. Aggregated particles are removed by sieving to obtain the soil conditioner for saline-alkali land.
[0127] Comparative Example 3
[0128] This comparative example prepares a core-shell structured saline-alkali soil conditioner, and its preparation method is basically the same as that in Example 1, except that Na... + Selective capture kernel and Ca 2+ / Mg 2+ No porous biochar separator is placed between the sustained-release layers, so that Ca 2+ / Mg 2+ The sustained-release layer is directly set on Na +Selective trapping of the outer core was used to investigate the effect of porous biochar isolation layers on Ca. 2+ / Mg 2+ To Na + The selective trapping effect on kernel migration, specifically prepared by the following methods:
[0129] S1~S5: Prepare short-chain polyether functionalized Biochar@UiO-66-NH2 materials according to the methods in steps S1~S5 of Example 1;
[0130] S6, Na + Selective capture kernel shaping: The Na obtained in step S5 + Selective capture material is mixed with deionized water and granulated by wet granulation. After granulation, Na+ is controlled by sieving. + Selective capture of kernel particles with a diameter of 0.65 mm was performed, and the resulting particles were dried at 60 °C for 12 h to obtain Na. + Selectively capture the kernel;
[0131] S7. Soil conditioner molding and post-treatment: Without performing the porous biochar isolation layer coating step in Example 1, calcium sulfate and magnesium sulfate are mixed at a mass ratio of 3:1, and starch is added as a slow-release coating material to prepare Ca... 2+ / Mg 2+ Slow-release coated slurry, Na obtained in step S6 + Selective capture kernels are placed directly in the fluidized bed, and Ca is captured by spray coating. 2+ / Mg 2+ Slow-release coated slurry directly coated with Na + Selective capture of the outer nucleus, forming a 0.50 mm thick Ca layer by controlling the coating amount. 2+ / Mg 2+ After the slow-release layer is coated, it is dried at 60℃ for 12 hours. Aggregated particles are removed by sieving to obtain the soil conditioner for saline-alkali land.
[0132] Comparative Example 4
[0133] This comparative example prepares a soil conditioner for saline-alkali land. The preparation method is basically the same as that in Example 1, except that Ca is not added. 2+ / Mg 2+ Sustained-release layer, retaining only Na + Selective trapping of the core and porous biochar isolation layer to investigate Ca² + / Mg² + Slow-release layer adsorbs Na from soil colloids + The promoting effect of the displacement process, and specific preparation methods include:
[0134] S1~S6, Prepare Na according to steps S1~S6 in Example 1.+ Selective core capture was achieved using porous biochar at a mass ratio of 1:0.5 to UiO-66-NH2, with carboxyl-terminated polyethylene glycol having a number-average molecular weight of 400, and short-chain polyether grafting amounting to 4% of the mass of UiO-66-NH2. Na... + The selectively captured kernel particle size is controlled to be 0.65 mm;
[0135] S7. Construction and post-processing of porous biochar isolation layer: Following the method in step S7 of Example 1, porous biochar is prepared into a biochar slurry with a mass concentration of 10%. The Na obtained in step S6 is then... + Selective capture nuclei are placed in a fluidized bed and spray-coated with biochar slurry. By controlling the spray rate and the number of coating cycles, Na... + A porous biochar isolation layer with a thickness of 0.20 mm was formed on the surface of the selectively captured core. After coating, it was dried at 60℃ for 6 hours, and the aggregated particles were removed by sieving to obtain a soil conditioner for saline-alkali land.
[0136] Comparative Example 5
[0137] This comparative example prepares a soil conditioner for saline-alkali land. The preparation method is basically the same as that in Example 1, except that Na is not used. + Selective trapping kernel, porous biochar isolation layer and Ca 2+ / Mg 2+ The spatial distribution structure of the sustained-release layer, instead of Na + Selective capture materials and Ca 2+ / Mg 2+ The source was directly mixed and then granulated to investigate Ca. 2+ / Mg 2+ and Na + The competitive ion mass transfer effect generated when selectively trapping materials are in direct contact, and specific preparation methods include:
[0138] S1~S5: Prepare short-chain polyether-functionalized Biochar@UiO-66-NH2 materials according to steps S1~S5 in Example 1, and obtain Na + Selective material capture;
[0139] S6, Ca 2+ / Mg 2+ with Na + Selective capture material mixing: The Na obtained in step S5 + Selective capture materials, calcium sulfate, and magnesium sulfate are mixed, wherein the mass ratio of calcium sulfate to magnesium sulfate is 3:1, and the total mass of calcium sulfate and magnesium sulfate is controlled relative to Na. + The selective capture materials were mixed at a mass ratio of 1:2 using mechanical stirring for 30 minutes, allowing calcium sulfate, magnesium sulfate, and Na to react.+ Selectively captures uniformly mixed materials;
[0140] S7. Granulation: Add deionized water to the mixture obtained in step S6 and form granules by wet granulation. After granulation, the particle size is controlled to be 0.65 mm by sieving. The obtained granules are dried at 60°C for 12 hours.
[0141] S8. Post-processing: The dried granules are sieved to remove agglomerated particles, yielding Ca. 2+ / Mg 2+ with Na + Selective capture materials are directly mixed to form a soil conditioner for saline-alkali land. The resulting soil conditioner contains Ca. 2+ / Mg 2+ Source and Na + The selectively captured material is in direct contact, without a separate porous biochar isolation layer or an external slow-release shell.
[0142] Experimental Example 1: Na + Ca 2+ and Mg 2+ Single-ion adsorption performance test: This experiment was used to evaluate the soil conditioner obtained in the examples and comparative examples for its adsorption of Na+. + Ca 2+ and Mg 2+ To assess the adsorption capacity, 0.500 g of each of the soil conditioner obtained in the examples and comparative examples were weighed and added to 50 mL of 100 mg / L NaCl, CaCl2, and MgCl2 solutions, respectively, with a solid-liquid ratio of 1:100. The mixtures were placed in a constant-temperature shaker and shaken at 25 °C and 150 r / min for 24 h. After shaking, the mixtures were filtered through a 0.45 μm filter membrane, and the Na+ content in the filtrate was measured. + Ca 2+ and Mg 2+ The remaining concentration of Na + Concentration was determined using flame atomic absorption spectrophotometry or inductively coupled plasma atomic emission spectrometry; Ca 2+ and Mg 2+ Concentrations were determined using inductively coupled plasma atomic emission spectrometry (ICP-AES), and the equilibrium adsorption capacity of each ion was calculated using the following formula:
[0143] ;
[0144] In the formula: qi is the equilibrium adsorption capacity of the i-th ion, mg / g; Ci,0 is the initial concentration of the i-th ion before adsorption, mg / L; Ci,e is the concentration of the i-th ion after adsorption equilibrium, mg / L; V is the solution volume, L; m is the mass of the soil conditioner, g.
[0145] Figure 1 Na is used in the embodiments and comparative examples of the present invention. + Ca 2+ and Mg 2+ The graph shows the residual concentration in the filtrate. Figure 2 Na is used in the embodiments and comparative examples of the present invention. + Ca 2+ and Mg 2+ The adsorption results are shown in the figure, for Na in Examples 1-5. + The equilibrium adsorption capacities were 8.20, 8.30, 8.50, 8.10, and 8.20 mg / g, respectively, generally falling within the range of 8.10–8.50 mg / g. This indicates that after functionalizing UiO-66-NH2 with porous biochar and further functionalizing it with short-chain polyethers, the resulting Na… + Selective trapping materials have relatively stable Na + Capture capability, wherein, in Example 3, Na + The adsorption capacity reached 8.50 mg / g, the highest among Examples 1-5, indicating that the functionalization parameters used in Example 3 were more favorable for Na. + It enters the sub-nanometer channels of UiO-66-NH2 and reversibly interacts with oxygen-containing sites within the channels. The Na in the remaining examples... + The adsorption capacity is close to that of Example 1, indicating that within the set range of UiO-66-NH2 loading, PEG grafting parameters, Ca / Mg ratio, and isolation layer parameters, Na... + The capture performance showed good stability and no significant performance degradation was observed.
[0146] Comparative Example 1 demonstrates that the sub-nanometer channels of UiO-66-NH2 are Na + The basis of selective capture; Comparative Example 2 demonstrates that short-chain polyether functionalization can further modulate the local hydration environment and oxygen-containing weak coordination within the pores, reducing Ca2+. 2+ / Mg 2+ Competition; Comparative Example 3 shows that although the porous biochar isolation layer is not Na + The main active component is captured, but mass transfer of divalent ions to the nucleus is reduced; Comparative Example 4 illustrates that Ca... 2+ / Mg 2+ The main function of the slow-release layer is to provide a continuous supply of calcium in the soil system. 2+ / Mg 2+ Promotes soil colloidal Na+ exchange + Release; Comparative Example 5 further illustrates that when Ca 2+ / Mg 2+ Source and Na +When materials are in direct contact with selectively captured materials, significant competitive adsorption occurs; therefore, Ca2+ must be captured through core-shell spatial partitioning. 2+ / Mg 2+ Release area and Na + Spatial isolation of selectively captured regions.
[0147] Experimental Example 2: Na + / Ca 2+ The binary competitive selectivity test was used to evaluate the soil conditioners obtained in Examples 1-5 in Na... + and Ca 2+ Na under coexistence conditions + The selective capture capability of Ca was examined, with a focus on Ca. 2+ To Na + To assess the competitive impact of the capture process, 0.500 g of each of the soil conditioners obtained in Examples 1-5 were weighed and added to 50 mL of a solution containing Na. + and Ca 2+ In the mixed solution, Na + The initial concentration was set at 100 mg / L, Ca 2+ The initial concentration was set to 100 mg / L. The mixture was placed in a 25°C constant-temperature shaker and shaken at 150 r / min for 24 h. After shaking, the mixture was filtered through a 0.45 μm filter membrane, and the Na content in the filtrate was measured. + and Ca 2+ The concentration of Na was calculated according to the method described in Experimental Example 1. + and Ca 2+ The equilibrium adsorption capacity was determined, and the partition coefficient was used to evaluate the competitive selectivity of the two ions:
[0148] ;
[0149] Where Di is the partition coefficient of the i-th ion;
[0150] Na + Relative to Ca 2+ The selectivity coefficient is calculated according to the following formula:
[0151] ;
[0152] Where: D Na for Na + Allocation coefficient; D Ca For Ca 2+ Allocation coefficient;
[0153] Experimental Example 3: Na + / Mg 2+ Binary competitive selectivity test: This experiment was used to evaluate the soil conditioners obtained in Examples 1-5 in Na...+ and Mg 2+ Na under coexistence conditions + The selective capture capability of Mg was examined, with a focus on Mg. 2+ To Na + To assess the competitive impact of the capture process, 0.500 g of each of the soil conditioners obtained in Examples 1-5 were weighed and added to 50 mL of a solution containing Na. + and Mg 2+ In the mixed solution, Na + The initial concentration was set at 100 mg / L, Mg 2+ The initial concentration was set to 100 mg / L. The mixture was placed in a 25°C constant-temperature shaker and shaken at 150 r / min for 24 h. After shaking, the mixture was filtered through a 0.45 μm filter membrane, and the Na content in the filtrate was measured. + and Mg 2+ Concentration, calculate Na according to the calculation method in Experiment Example 1. + and Mg 2+ The equilibrium adsorption capacity and removal rate of Na were calculated. + and Mg 2+ The allocation coefficient is calculated according to the following formula for Na. + Compared to Mg 2+ Selectivity coefficient:
[0154] ;
[0155] Where: D Na for Na + Allocation coefficient; D Mg Mg 2+ Allocation coefficient;
[0156] Figure 3 The soil conditioners prepared for the embodiments and comparative examples of this invention have the following effects on Na+. + The results of selective adsorption are shown in the figure. Examples 1-5 all exhibit high Na⁺ capture capacity, where Na⁺… + The adsorption capacity was 8.10~8.50 mg / g, significantly higher than that of Comparative Example 1 without UiO-66-NH2, indicating that the sub-nanopores formed by UiO-66-NH2 can enhance Na adsorption. + Selective mass transfer and capture. Comparative Example 2: Na + The adsorption amount decreased and Ca 2+ Mg 2+ The increased adsorption capacity indicates that the functionalization of short-chain polyethers can enhance Na adsorption by regulating the local hydration environment of the pores and the weak oxygen-containing coordination. + Compared to the selectivity of divalent ions, Comparative Example 3 shows that, in the absence of a porous biochar separator, although Na... +The adsorption amount changed little, but Ca 2+ Mg 2+ Easier access to the core indicates that the isolation layer primarily functions as a barrier to mass transfer in space. (Comparative Example 5, Ca...) 2+ / Mg 2+ with Na + After selective materials are directly mixed, Na + The adsorption capacity decreased to 6.90 mg / g, while Ca 2+ Mg 2+ The adsorption capacity increased to 4.80 mg / g and 4.40 mg / g, respectively, indicating that direct mixing would lead to significant competition for divalent ions.
[0157] Migration tests show that Ca in Example 1 2+ Mg 2+ The kernel penetration rates were 8.5% and 7.8%, respectively, while Na... + The migration rate to the kernel reached 63.5%; in Comparative Example 5, Na + The migration rate to the kernel was only 31.8%, Ca 2+ Mg 2+ The penetration rates reached 42.5% and 39.6%, respectively. These results indicate that the present invention, through Ca... 2+ / Mg 2+ Slow-release layer, porous biochar isolation layer, Na + Selectively capturing the kernel's spatial partitioning structure allows Ca... 2+ / Mg 2+ It can migrate into soil colloids and replace Na. + And the released Na + It can preferentially migrate to the kernel while suppressing Ca 2+ / Mg 2+ It enters the kernel, thus forming Ca. 2+ / Mg 2+ Outward displacement, Na + The inward-captured directional ion migration process enables the continuous desodium removal from saline-alkali soils.
[0158] Experiment Example 4:
[0159] Ca 2+ and Mg 2+ Core migration rate: Three parallel samples were taken from each group of soil conditioners prepared in Examples 1-5 and Comparative Examples 1-5. The samples were placed in deionized water and extracted at 25±2℃. Samples were taken at 1d, 3d, 7d, 14d, and 30d. At the corresponding time points, the soil conditioner was removed, and the outer Ca2+ was removed sequentially by mechanical stripping or layer-by-layer dissolution. 2+ / Mg 2+ A slow-release layer and an intermediate porous biochar isolation layer were used to obtain Na.+ Selectively capture the kernel, then acid digest the resulting kernel to remove the Ca2+. 2+ and Mg 2+ After being completely dissolved in the solution and brought to a final volume, the Ca in the core was determined using ICP-OES, ICP-MS, or atomic absorption spectrometry. 2+ and Mg 2+ The content, respectively denoted as M Ca,core and M Mg,core Simultaneously, unextracted soil conditioner from the same batch was subjected to acid digestion to determine its Ca content. 2+ and Mg 2+ The total content is denoted as M. Ca,total and M Mg,total Calculate the kernel mobility using the formula:
[0160] P Ca,core =M Ca,core / M Ca,total ×100%;
[0161] P Mg,core =M Mg,core / M Mg,total ×100%;
[0162] Na + Core migration rate test: Saline-alkali soil was used as the test soil sample, and the exchangeable Na content of the soil before treatment was measured. + The soil conditioners from Examples 1-5 and Comparative Examples 1-5 were added to the soil at the same dosage. The soil moisture content was adjusted to 60%-70% of field capacity at 25±2℃. A cultivation experiment was conducted, and soil infiltrates or pore water were collected at 1, 3, 7, 14, and 30 days. The Na content was determined using ICP-OES, ICP-MS, or atomic absorption spectrometry. + Concentration, based on the volume of exudate and Na in each time period. + Na released into the soil water system from soil colloids during the concentration calculation experiment + Total M Na,release Simultaneously, at the corresponding time points, the soil conditioner was removed, and the surface of the particles was washed with deionized water to remove Ca in sequence. 2+ / Mg 2+ A slow-release layer and a porous biochar isolation layer were used to obtain Na. + Selective capture of the nucleus is achieved by eluting the nucleus with ion exchange using NH4Cl or KCl solution, allowing the captured Na+ in the nucleus to be eluted. + Released into the extract, and after adjusting the volume, the Na content in the extract was measured. + Concentration, and calculate the actual Na captured by the kernel. + Mass M Na,core Calculate the kernel mobility using the formula:
[0163] P Na,core =M Na,core / M Na,release ×100%;
[0164] Figure 4 Na in the soil conditioners prepared for the embodiments and comparative examples of the present invention + Ca 2+ and Mg 2+ The mobility results are shown in the figure, representing Ca in Example 1. 2+ Mg 2+ The kernel penetration rates were 8.5% and 7.8%, respectively, while Na... + The migration rate to the kernel reached 63.5%; in Comparative Example 5, Na + The migration rate to the kernel was only 31.8%, Ca 2+ Mg 2+ The penetration rates reached 42.5% and 39.6%, respectively. These results indicate that the present invention, through Ca... 2+ / Mg 2+ Slow-release layer, porous biochar isolation layer, Na + Selectively capturing the kernel's spatial partitioning structure allows Ca... 2+ / Mg 2+ It can migrate into soil colloids and replace Na. + And the released Na + It can preferentially migrate to the kernel while suppressing Ca 2+ / Mg 2+ It enters the kernel, thus forming Ca. 2+ / Mg 2+ Outward displacement, Na + The inward-captured directional ion migration process enables the continuous desodium removal from saline-alkali soils.
[0165] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention.
[0166] The present invention and its embodiments have been described above. This description is not restrictive, and the accompanying drawings are only one embodiment of the present invention. The actual application is not limited to this. In conclusion, if those skilled in the art are inspired by this description and design similar methods and embodiments without departing from the spirit of the present invention, they should all fall within the protection scope of the present invention.
Claims
1. An environmentally friendly soil conditioner for saline-alkali land, characterized in that: The soil conditioner includes Na + Selective capture kernel, located in the Na + Selective capture of the porous biochar isolation layer outside the core and Ca located outside the porous biochar isolation layer 2+ / Mg 2+ Sustained-release layer; the Na + The selective trapping core comprises a porous biochar framework and a functionalized UiO-66 material supported on the porous biochar framework. The functionalized UiO-66 material has a sub-nanometer pore structure and oxygen-containing weak coordination sites at the pore openings and / or accessible pore regions. The functionalized UiO-66 material is UiO-66-NH2. Short-chain polyethers are grafted onto the pore openings and / or accessible pore regions of the functionalized UiO-66 material. These short-chain polyethers are covalently linked to the amino sites of UiO-66-NH2, and the ether oxygen in the short-chain polyether constitutes the oxygen-containing weak coordination sites. The Na... + Selective capture kernel for Na + Ca 2+ and Mg 2+ The multi-ion competing system constitutes Na + Preferred adsorption characteristics.
2. The environmentally friendly saline-alkali soil conditioner according to claim 1, characterized in that: The short-chain polyether is carboxyl-terminated polyethylene glycol, and the number average molecular weight of the carboxyl-terminated polyethylene glycol is 200-600; the mass of the short-chain polyether is 1-10% of the mass of UiO-66-NH2.
3. The environmentally friendly saline-alkali soil conditioner according to claim 2, characterized in that: The Ca 2+ / Mg 2+ The sustained-release layer includes Ca 2+ Source and Mg 2+ Source; the Ca 2+ / Mg 2+ The sustained-release layer comprises one or both of calcium sulfate and magnesium sulfate; the Ca 2+ / Mg 2+ The sustained-release layer also includes a sustained-release coating material coated on the surface of calcium sulfate and / or magnesium sulfate particles; the sustained-release coating material is at least one of porous biochar, starch-based material, cellulose-based material, and natural polymer material; the Ca 2 + / Mg 2+ Ca in the sustained-release layer 2+ Source and Mg 2+ The mass ratio of the source is 10:1 to 1:
10.
4. The environmentally friendly saline-alkali soil conditioner according to claim 3, characterized in that: The soil conditioner has a core-shell structure, and the Na... + The selectively trapping core is located at the center of the particle, and the porous biochar isolation layer is located within the Na+. + Selective capture kernel and Ca 2+ / Mg 2+ Between the sustained-release layers, the Ca 2+ / Mg 2+ The slow-release layer forms the outer shell of the soil conditioner; The Na + The selectively trapping kernel has a particle size of 0.2~1.0 mm, and the porous biochar isolation layer has a thickness of 0.05~0.5 mm. 2+ / Mg 2+ The thickness of the sustained-release layer is 0.1~1.0 mm.
5. A method for preparing an environmentally friendly saline-alkali soil conditioner according to claim 4, characterized in that: Specifically, the steps include the following: S1. Preparation of porous biochar: The biomass raw material is pyrolyzed and carbonized to obtain initial biochar, and the initial biochar is activated by an activator to obtain porous biochar. Preparation of S2 and UiO-66-NH2 precursor solutions: Zirconium source, 2-aminoterephthalic acid and regulator are added to an organic solvent and mixed to obtain UiO-66-NH2 precursor solution; S3, UiO-66-NH2 in-situ loading: The porous biochar prepared in step S1 is added to the UiO-66-NH2 precursor solution prepared in step S2 to allow UiO-66-NH2 to nucleate and grow in situ, thus obtaining Biochar@UiO-66-NH2 composite material. S4, UiO-66-NH2 activation: The Biochar@UiO-66-NH2 composite material prepared in step S3 is washed, solvent replaced and vacuum activated for later use; S5. Pore Functionalization: The Biochar@UiO-66-NH2 composite material activated in step S4 is coupled with a carboxyl-terminated short-chain polyether to obtain Na. + Selective material capture; S6, Na + Selective core shaping: The Na prepared in step S5 + Selective capture of materials is granulated and shaped to obtain Na. + Selectively capture the kernel; S7. Construction of the porous biochar isolation layer: The porous biochar prepared in step S1 is made into a biochar slurry with a mass concentration of 10%. The Na prepared in step S6 is then... + Selective capture nuclei are placed in a fluidized bed and spray-coated with biochar slurry, allowing Na+ to be captured. + A porous biochar isolation layer is formed on the surface of the selectively captured kernel, and then dried for later use. S8. Soil conditioner molding and post-treatment: Ca... 2+ Source and Mg 2+ Sources were mixed, and a slow-release coating material was added to prepare Ca. 2+ / Mg 2 + Slow-release coated slurry, which contains Na treated in step S7 + Selective capture particles are placed in a fluidized bed and Ca is captured by spray coating. 2+ / Mg 2+ Slow-release coated slurry is applied to the outside of the porous biochar isolation layer. After coating, Ca is formed. 2+ / Mg 2+ The slow-release layer is dried to obtain an environmentally friendly saline-alkali soil conditioner.
6. The method for preparing an environmentally friendly saline-alkali soil conditioner according to claim 5, characterized in that: In step S1, the biomass raw material is pyrolyzed at 450~600℃ under an inert atmosphere for 1~3h; the initial biochar and activator are activated at a mass ratio of 1:1~1:3, the activation temperature is 650~750℃, and the activation time is 1-1.5h.
7. The method for preparing an environmentally friendly saline-alkali soil conditioner according to claim 6, characterized in that: In step S2, the molar ratio of the zirconium source to 2-aminoterephthalic acid is 1:0.8 to 1:1.2, and the molar ratio of the regulator to the zirconium source is 20 to 60:
1.
8. The method for preparing an environmentally friendly saline-alkali soil conditioner according to claim 7, characterized in that: In step S3, the mass ratio of porous biochar to UiO-66-NH2 in the obtained Biochar@UiO-66-NH2 composite material is 1:0.2~1:1; in step S3, the in-situ nucleation growth temperature is 100~140℃ and the time is 12~36h.
9. The method for preparing an environmentally friendly saline-alkali soil conditioner according to claim 8, characterized in that: In step S5, the grafting amount of the short-chain polyether is 2 to 6% of the mass of UiO-66-NH2.
10. The method for preparing an environmentally friendly saline-alkali soil conditioner according to claim 9, characterized in that: In step S8, the Ca 2+ Source, Mg 2+ The mass ratio between the source and the sustained-release coating material is 10:1:0.8 to 1:10:1.2; the Ca 2 + / Mg 2+ The solid content of the slow-release coated slurry is 45-55%.